How a Digital Learning Become a Teaching Media in Hotel Accommodation Subject? - Fitriyani, Endah; Fitria, Dea; Islamiyah, Indah; Pratiwi, Ilma Indriasri (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2022)
Vocational High School (SMK) graduates are directed to acquire certain skills that are needed by the industrial world, so that in the learning process, growing experience, visual stimulation, affective awareness, extracting cognitive information, and developing psychomotor skills is a must. The continuous learning process aims to support vocational development which includes exploring, strengthening, and preserving the talents of a student in pursuing a career in the world of work in vocational schools that is balanced with practical and theoretical abilities, this ability can be proven by a certificate of competence by each graduate. Digital learning for hospitality subjects at SMK Pariwisata is very much needed to support the practical abilities of students. The purpose of this research is to examine the development of a digital learning model of the hospitality learning which is expected to be able to produce a virtual space. The data techniques used were observation and interviews, using this type of qualitative research.